Greenwashing and Sustainable Consumption in India: A Socio-legal Study of Consumer Perception, Behaviour, and the Legal Enforcement Gap - Pooja Devi; Shikha Sharma (Sriwijaya Law Review, 2026)
Sustainable marketing has reshaped recent consumption behaviours. As global awareness of green living grows, businesses are gradually promoting the “green badge" to coincide with consumer values and the Sustainable Development Goals (SDGs). This eco trend has given rise to greenwashing, an unfair trade practice that deceives consumers about a product or service's environmental benefits, undermining consumer loyalty and decision-making. The present study empirically investigates the rising consumer awareness and the limited enforcement capacity, compounded by procedural complexities, that undermine consumer participation. A mixed-methods approach has been used to analyse descriptive statistics, cross-tabulations, and qualitative responses by theme to understand consumer awareness, purchasing behaviour, experiences of greenwashing, and enforcement of legal rights. In the present study, researchers have focused on and elaborated on two factors -age-group and Income-group of the consumer to understand the gap between awareness and enforcement of legal rights. The results show that a majority of respondents (87%) are aware of the concepts of green consumption and greenwashing, but this awareness does not translate into legal action against greenwashing. The study adds to the existing literature on consumer behaviour by empirically demonstrating the awareness-action paradox in the context of sustainability and the key role of regulatory and procedural barriers in mediating consumer behaviour in the marketplace.